Real-Time Vital Sign Detection using a 77 GHz FMCW Radar - Ganzle, Thomas; Klock, Clemens; Heuschkel, Karsten (2022 IEEE-EMBS Conference on Biomedical Engineering and Sciences (IECBES), 2022)
This work focused on vital sign monitoring of a sleeping subject in real-time using the AWR1642 Boost of Texas Instruments. A newly designed signal processing chain is proposed to obtain a clearly recognizable heart and breath signal from the raw radar data. The averaged breath and heart rates were then calculated from these breath and heart signals. For the evaluation of these frequencies, the pulse of the test person was measured parallel to the radar measurement with a Garmin Forerunner 735XT. The results of the research show, that it would be possible to implement a monitoring system with the help of a radar sensor.